TRUBOBETONNYE KOLONNY DLYa MNOGOETAZhNYKh ZDANIY - A L Krishan (Structural Mechanics of Engineering Constructions and Buildings, 2009)
THE CONCRETE-FILLED STEEL TUBE COLUMNS FOR HIGH-RISE BUILDINGS A.L. Krishan The concrete-filled steel tube columns should be used in the structures of hiqh-rise buildings. The experimental and theoretical researches of new structures of concrete-filled steel tube columns with pressed structure of concrete are executed. The results of experiences testify to its high bearing capacity.